Pengaruh Current Ratio dan Debt to Equity Ratio Terhadap Return on Asset pada BPRS Madinah - Akmalur Rijal; Lia Indriati Ningrum (CV. Ulil Albab Corp, 2023)
Financial pay statements are required by both conventional and Islamic banks in order to provide report users with important information about the company's performance, cash flow, and financial status. But it goes beyond financial statements; if financial ratios are used to analyze the financial accounts, valuable information can be gleaned. The aim of this research was to ascertain the impact of the Debt to Equity Ratio and Current Ratio on Return on Assets at the BPRS Madinah Lamongan over the 2020 timeframe. This study employed a quantitative methodology, using a sample of the BPS Madinah Lamongan financial statements for the year 2020 as the population of financial statements. Multiple linear analysis is used in this study to determine how independent variables affect the independent variable. In order to determine the relationship between two independent variables together or more with one independent variable, the F test simultaneously evaluates the independent variables in the independent variable and the correlation coefficient. The f test results indicated that the current ratio and the debt to equity ratio both had a substantial impact on return on assets at the same time, with an icount of (1.357) and a t table of (199) with a significance of (0.519) > (0.05).